Soil heavy metal lead pollution and its stabilization remediation technology. (December 2020) - Shao, Youyuan; Yan, Tao; Wang, Kai; Huang, Simin; Yuan, Wuzhi; Qin, Frank G.F.
Abstract: In the process of energy utilization, heavy metals are released into the environment in the form of flue gas or slag due to the combustion of some heavy metals-bearing fuels and migrated among the atmosphere, water and soil, causing various environmental pollution, such as fossil fuels (like coal), heavy oil, leaded gasoline, garbage power generation, etc. Soil is the ultimate receptor of heavy metal pollutants. In this paper, the pollution, harm and development trend of heavy metals in soil are briefly introduced. The mechanism and path of the formation of pyromorphite from heavy metal lead in soil are mainly elaborated. The similarities and differences between the natural formation and artificial synthesis of pyromorphite are compared. The stability of pyromorphite in water or soil is discussed. The samples of synthetic pyromorphite are obtained through experiments, and the experimental samples are analyzed and proved by adopting XRD analysis method. The results show that the synthetic pyromorphite is short in time, low in cost and stable in water or soil. Therefore, it can be expected that the application of fertilizer containing phosphorus and chlorine elements can serve as an important measure for remediation of heavy metal lead contaminated soil in the future.